Efficacy of a three‐day training course in endoscopic submucosal dissection using a live porcine model: a prospective evaluation. Issue 9 (1st November 2018) - Chapelle, Nicolas; Musquer, Nicolas; Métivier-Cesbron, Elodie; Luet, Dominique; Volteau, Christelle; Le Rhun, Marc; Coron, Emmanuel
Abstract : Background: Endoscopic submucosal dissection is currently regarded as the method of choice for the resection of superficial tumours. The objective of our study was to evaluate prospectively the efficiency of an endoscopic submucosal dissection training course using live anaesthetised pigs. Methods: Fourteen novice endoscopists participated in three gastric endoscopic submucosal dissection training courses on anaesthetised pigs. Each trainee resected five 'fake' antral lesions. Resected specimen sizes, endoscopic submucosal dissection speeds and the complication rate were evaluated prospectively. Results: Among the 70 procedures performed, 58 could be analysed. There was a strong increase in endoscopic submucosal dissection speed (from 9.7 mm 2 /minute to 30.4 mm 2 /minute) during the sessions, marked between the first two endoscopic submucosal dissections compared with the fourth and fifth. There was a significant relation between the surface area of the resected lesion and procedure speed ( P  < 0.0001). The complication rate was 8.6%. Conclusion: There is a clear benefit from endoscopic submucosal dissection training courses on animal models. Improved endoscopist capability is evident from the third endoscopic submucosal dissection. These data validate the indispensable nature of dedicated training courses and echo the European Society of Gastrointestinal Endoscopy proposition for multistep learning, beginning on animal models.